2021
DOI: 10.5194/tc-2021-225
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Propagating information from snow observations with CrocO ensemble data assimilation system: a 10-years case study over a snow depth observation network

Abstract: Abstract. The mountainous snow cover is highly variable at all temporal and spatial scales. Snowpack models only imperfectly represent this variability, because of uncertain meteorological inputs, physical parameterisations, and unresolved terrain features. In-situ observations of the height of snow (HS), despite their limited representativeness, could help constrain intermediate and large scale modelling errors by means of data assimilation. In this work, we assimilate HS observations from an in-situ network … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 74 publications
3
8
0
Order By: Relevance
“…While precipitation biases play an important role in these difference, errors in modelled snow depth are influenced by many processes in snowpack models including the parameterization of snow density (Helfricht et al, 2018), handling of precipitation type, and simulating settlement processes. While this simple precipitation-adjustment method is not the state of the art in data assimilation (Cluzet et al, 2022;Winstral et al, 2018), it provides a simple approach to analyse the impact of precipitation errors in different regions.…”
Section: Adjusting Precipitation Inputs Of the Simulated Snow Profilesmentioning
confidence: 99%
See 3 more Smart Citations
“…While precipitation biases play an important role in these difference, errors in modelled snow depth are influenced by many processes in snowpack models including the parameterization of snow density (Helfricht et al, 2018), handling of precipitation type, and simulating settlement processes. While this simple precipitation-adjustment method is not the state of the art in data assimilation (Cluzet et al, 2022;Winstral et al, 2018), it provides a simple approach to analyse the impact of precipitation errors in different regions.…”
Section: Adjusting Precipitation Inputs Of the Simulated Snow Profilesmentioning
confidence: 99%
“…The precipitation-adjustment method applied in this study is likely insufficient for an operational model system, as it assumes a constant bias over time and oversimplifies the causes of snow depth errors. More advanced data assimilation methods have recently been suggested for snowpack models (Largeron et al, 2020), including methods presented by Winstral et al (2018) and Cluzet et al (2022) that use similar snow observation networks in Europe. Cluzet et al (2022) found assimilating snow depth observations improved simulations in areas of France with relatively sparse observations but that the density of snow observations was correlated with the density of precipitation observations.…”
Section: Implications For Snowpack Modellingmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the harsh environmental conditions that often prevail in snow-dominated areas, in situ monitoring of the snow-E. Alonso- González et al: MuSA: the Multiple Snow Data Assimilation System (v1.0) pack based on automatic devices and weather stations is both costly and logistically challenging. In addition, due to the spatiotemporal variability in the snowpack (López-Moreno et al, 2011), even dense monitoring networks may suffer from a lack of representativeness (Molotch and Bales, 2006;Cluzet et al, 2022). Yet, estimating SWE spatial distribution is important to make accurate predictions of snowmelt runoff in alpine catchments.…”
Section: Introductionmentioning
confidence: 99%